TRANSCOV, a multidisciplinary project to evaluate long distance COVID patients transfers. (20th October 2021) - Grimaud, O; Girault, A; Laude, L; Sirven, N; Cucharero Atienza, P; Fermanian, C; Elgharabawy, Y; Ramanantsoa, J; Bayat, S; Leray, E
Abstract: Background: Faced with an abrupt surge of severe COVID patients in March and April 2020, intensive care units (ICU) from four French regions transferred around 660 patients towards six other regions and four neighbouring countries. The intensity and the diversity of the vectors used (plane, helicopter, train, ambulance), during this wave of medical evacuations make it an unprecedented event. The aim of TRANSCOV is to examine the impact of long distance transfers on patient's health and to understand how actors collaborated to overcome clinical and logistical challenges. Methods: TRANSCOV is made of three disciplinary components: 1) interviews with clinicians and health authorities staff involved in the organisation and realisation of the transfers as part of the qualitative component; 2) a retrospective cohort collecting clinical parameters and pathway details before during and after transfer; 3) a collection of data regarding human and logistical resources mobilised during transfers as part of an economical evaluation. Results: Preliminary results indicate that prior experience in medical evacuations proved useful to collaborate effectively in the exceptional circumstances prevailing in spring 2020. Clinicians had to establish quickly eligibility criteria for transfer. Actors' opinions may vary on the appropriateness of vectors to transfer isolated (e.g. via helicopter) or grouped (train) patients. Early epidemiological data suggest that transferred patients were younger and experienced comparable, if not lower, in-hospital mortality compared to other patients. The economic evaluation is in progress. Conclusions: Initial results indicate that effective collaborations led to the selection of clinically eligible patients and the realisation of safe distant transfers. Key messages: Healthcare organisations have been able to adapt and create organizational innovations to respond to COVID-19. Multidisciplinary approaches are appropriate to evaluate such complex innovations.